Analisis Perencanaan Produksi Molring di Home Industry Tasbar Kabupaten Tasikmalaya - Ernawati; Awalia, Niken Martianur (LPPM Sekolah Tinggi Teknologi Cipasung, 2025)
Tasbar was founded by Enung Nurjanah which produces snacks, namely molring, located in Leuwisari District, Tasikmalaya Regency. Tasbar experienced a problem, namely delays in producing molrings due to not estimating how much time it would take to produce an order when the order was finished and could be sent to the customer. This resulted in a 21% decrease in customers. Therefore, the method used is a moving average to predict the production planning process in inventory management. As a result, 160 kg of product can be produced per month, material for inventory management to respond to demand patterns, so that it can be used as a reference for make to stock production.